2016
DOI: 10.1007/s10739-016-9439-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanists Must be Holists Too! Perspectives from Circadian Biology

Abstract: The pursuit of mechanistic explanations in biology has produced a great deal of knowledge about the parts, operations, and organization of mechanisms taken to be responsible for biological phenomena. Holist critics have often raised important criticisms of proposed mechanistic explanations, but until recently holists have not had alternative research strategies through which to advance explanations. This paper argues both that the results of mechanistic strategies has forced mechanists to confront ways in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…But this is not obviously the case. Bechtel (2016) has asserted that “reductionists must be holists too!,” arguing that any worthwhile explanation of a system at a lower level must make reference to systemic properties and organization – otherwise, one would never know which kinds of organization must be implemented at the lower level. Moreover, it has always been a part of Bechtel’s program that mechanistic explanations must go hand-in-hand with dynamical explanations in order to account for phenomena ( Bechtel and Abrahamsen, 2010 ).…”
Section: Dimensions Of the Reduction And Emergence Debatementioning
confidence: 99%
“…But this is not obviously the case. Bechtel (2016) has asserted that “reductionists must be holists too!,” arguing that any worthwhile explanation of a system at a lower level must make reference to systemic properties and organization – otherwise, one would never know which kinds of organization must be implemented at the lower level. Moreover, it has always been a part of Bechtel’s program that mechanistic explanations must go hand-in-hand with dynamical explanations in order to account for phenomena ( Bechtel and Abrahamsen, 2010 ).…”
Section: Dimensions Of the Reduction And Emergence Debatementioning
confidence: 99%
“…Mechanists have argued that mechanism identity is explanandum relative (Craver [2007]), that mechanism description should be sensitive to explanatory context (Craver [2001]), and for a variety of ways in which dynamical and network-based models of systems can interact productively with mechanistic research. Abrahamsen ([2009], [2010]; Bechtel, [2016]) in particular have argued that understanding dynamics, 'recomposing' the mechanism, and situating the mechanism in the environment (Roe and Baumgartner [2017]) are all important for understanding how a mechanism produces a phenomenon. 10 In discussion of reductionism, Wimsatt ([2006]) has suggested that interlevel correspondences within mechanisms will be heavily context-dependent.…”
Section: The Scope and Limits Of Mechanistic Explanationmentioning
confidence: 99%
“…This is primarily due to the difficulty of identifying the biological effect of variants identified as significantly associated with the disorder. More philosophically, it is becoming increasingly recognised that considering interactions across the whole system is required to understand mechanisms in biology [1], and this may be particularly the case for brain disorders [2]. In the rest of the article we will refer to GWAS because they are the focus of much genetic research in neuropsychiatric disorders at the moment, but the same issues apply to other genetic association studies.…”
Section: Introductionmentioning
confidence: 99%